2000
DOI: 10.1542/peds.105.2.e26
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Developmental Outcomes in Patients With Deformational Plagiocephaly

Abstract: ABSTRACT. Objectives. To determine whether there was an increased rate of later developmental delay in school-aged children who presented as infants with deformational plagiocephaly without obvious signs of delay at the time of initial evaluation.Methods. A retrospective medical record review of 254 patients evaluated at the Craniofacial Center of the Children's Hospital and Regional Medical Center in Seattle, Washington, from 1980 through 1991 was completed. Consenting patient families were interviewed via te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
5
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(125 citation statements)
references
References 14 publications
3
106
5
7
Order By: Relevance
“…The frequency of PP then begins to level down, with a normalization in shape by 6 months as the infant gains active control of the head. 39,44 Unfortunately, there has been an accompanying false increase in the rate of synostotic plagiocephaly due to misdiagnosis and a lack of ability to differentiate the 2 conditions, leading to unnecessary referrals. 26 Craniosynostosis is an important differential diagnosis, particularity the lambdoid type.…”
Section: Extent Of the Problemmentioning
confidence: 99%
“…The frequency of PP then begins to level down, with a normalization in shape by 6 months as the infant gains active control of the head. 39,44 Unfortunately, there has been an accompanying false increase in the rate of synostotic plagiocephaly due to misdiagnosis and a lack of ability to differentiate the 2 conditions, leading to unnecessary referrals. 26 Craniosynostosis is an important differential diagnosis, particularity the lambdoid type.…”
Section: Extent Of the Problemmentioning
confidence: 99%
“…Because of this poor compliance, a concern has arisen that they might limit cranial growth and subject the wearers to the risk, although slight, of increased intracranial pressure or direct brain injury. 33 This supposition was partially refuted in a small clinical study by Kelly, et al, 24 in which it was reported that craniofacial asymmetry was decreased by the molding helmet, whereas head circumference, maximal cranial length, and maximal cranial width measurements showed continuous growth of the skull. Kelly and coworkers estimated cranial growth by using two-dimensional measurements and a crude statistical method, however; thus, it is difficult to infer from their data the safety of threedimensional skull growth after helmet therapy.…”
Section: Treatment Of Positional Plagiocephalymentioning
confidence: 99%
“…25,[28][29][30] The passive molding helmet also compresses the protuberant area to some degree, depending on its fit and weight, and thus factors that can make the dif-ference between passive and active helmets become less significant. 31,33 All molding helmets-especially those with active compression-exert some degree of pressure on the skull, a feature that results in poor compliance when they are worn by infants and young children. In our experience, the application of these commercial helmets is very difficult clinically.…”
Section: Treatment Of Positional Plagiocephalymentioning
confidence: 99%
See 2 more Smart Citations